Adsorption of hyaluronic acid on solid supports: Role of pH and surface chemistry in thin film self-assembly - Choi, Jae-Hyeok (2016)
Owing to its biocompatibility, resistance to biofouling, and desirable physicochemical and biological properties, hyaluronic acid (HA) has been widely used to modify the surface of various materials. The role of various physicochemical factors in HA adsorption remains, however, to be clarified. Herein, we employed quartz crystal microbalance with dissipation (QCM-D) in order to investigate HA adsorption at different pH conditions onto three substrates—silicon oxide, amine-terminated self-assembled monolayer (SAM) on gold, and carboxylic acid-terminated SAM on gold. The QCM-D experiments indicated specific pH conditions where either strong or weak HA adsorption occurs. The morphology of the adsorbed HA layers was investigated by atomic force microscopy (AFM), and we identified that strong HA adsorption produced a complete, homogenous and smooth HA layer, while weak HA adsorption resulted in rough and inhomogeneous HA layers. The observed specifics of the kinetics of HA adsorption, including a short initial linear phase and subsequent long non-linear phase, were described by using a mean-field kinetic model taking HA diffusion limitations and reconfiguration in the adsorbed state into account. The findings extend the physicochemical background of design strategies for improving the use of passive HA adsorption for surface modification applications.